Simultaneous determination of ivabradine, metoprolol and their metabolites in rat plasma by ultra-performance liquid chromatography tandem mass spectrometry and its application in a pharmacokinetic study. Issue 19 (7th October 2015) - Sun, Wei; Chen, Ruimin; Li, Wanshu; Zhang, Hui; Ye, Jifeng; Cui, Xiao; Huang, Chengke
<x xml:space="preserve">Abstract</x> A sensitive and rapid UPLC-MS/MS method was developed to determine ivabradine, metoprolol and their corresponding metabolites in rat plasma simultaneously.